2019
DOI: 10.1002/bmc.4608
|View full text |Cite
|
Sign up to set email alerts
|

Stability‐indicating HPLC method for simultaneous quantification of 14 impurities in excedrin tablet formulations and identification of new impurity by LC–MS in accelerated stability studies

Abstract: We developed novel stability-indicating HPLC method for simultaneous estimation of 14 impurities in excedrin tablet, a formulation with a combination of acetaminophen, aspirin, and caffeine. In addition, a new impurity that was generated through degradation of aspirin at high temperatures during the accelerated stability conditions was positively identified and confirmed, using liquid chromatography-mass spectrometry technique. The HPLC method was optimized using the Inertsustain C 18 , 250 × 4.6 mm, 5.0 μm co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The proposed method was validated as per International Conference on Harmonization guidelines and US Pharmacopeia (USP) Compendia (Horacio et al, 2018; ICH, 2005; Dongala, Katakam, et al, 2019; Dongala, Katari, et al, 2019a, 2019b; Ashok, Thirupathi, Ravindra Kumar, & Jayashree, 2017; Murthy, Srinivas, Kumar, & Mukkanti, 2011; Subramanian, Katari, Dongala, & Jonnalagadda, 2020; Palakurthi, Dongala, Yalavarthi, & Anireddy, 2019; Kumar et al, 2013a, 2013b; Dongala, Katakam, et al, 2019; Dongala & Palakurthi, 2019; Dongala, Palakurthi, et al, 2019) based on the industry standard equipment.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed method was validated as per International Conference on Harmonization guidelines and US Pharmacopeia (USP) Compendia (Horacio et al, 2018; ICH, 2005; Dongala, Katakam, et al, 2019; Dongala, Katari, et al, 2019a, 2019b; Ashok, Thirupathi, Ravindra Kumar, & Jayashree, 2017; Murthy, Srinivas, Kumar, & Mukkanti, 2011; Subramanian, Katari, Dongala, & Jonnalagadda, 2020; Palakurthi, Dongala, Yalavarthi, & Anireddy, 2019; Kumar et al, 2013a, 2013b; Dongala, Katakam, et al, 2019; Dongala & Palakurthi, 2019; Dongala, Palakurthi, et al, 2019) based on the industry standard equipment.…”
Section: Resultsmentioning
confidence: 99%
“…According to US FDA requirements (Guidance for industry, analytical procedures, and methods validation, FDA, 2000), a SIM [23][24][25][26][27][28][29][30][31][32] is described as a validated analytical procedure that quantifies the drug, free from process impurities, excipients, and degradation products precisely and accurately. The US-FDA supports that all assay methods for stability should be stability-indicating.…”
Section: Uncoated or Film-coated Tabletsmentioning
confidence: 99%
“…In the current study, we have proposed an improved and alternative quality by design-based RP-HPLC method for the simultaneous determination of carbidopa, levodopa, and their impurities with a combination of entacapone in solid oral dosage forms. The purpose of the stabilityindicating analytical method is to provide evidence on how the quality of a drug substance or drug product varies with time under the influence of various environmental factors such as temperature, humidity, and light, and to establish a retest period for the drug substance or shelf life for the drug product and recommended storage condition [17][18][19][20]. Dongala et al [21] have demonstrated the importance of stability-indicating in the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%